An Assessment of Nigerian Foreign Policy during Babangida's Regime 1985-1993 - Mohammed, Garba; B. Shehuri, Ibrahim (Kashere Journal of Politics and International Relations, 2023)
The paper examines Nigeria's foreign policy during Babangida's Administration (19851993). This is imperative if external relations of a country are to be understood within the context of its foreign policy principles, statements and objectives which define her national interests. The paper examines the achievements and problems faced during Babangida's administration at both bilateral and multilateral levels from 1985-1993.The paper uses qualitative method to analyze data collected from secondary source. The objective is to discuss merit and demerit of Babangida's foreign policy. The paper used linkage theory which posits that there are linkages between foreign policy of a country, domestic and international environments. The findings of the paper revealed that there is the need to further boost and promote security and political relations between Nigeria and other countries. The paper recommends that there is the need to strengthen bilateral and multilateral interactions among countries.